Agricultural policy and the WTO Agreement: The Philippine Case - Cristina C. David (Philippine Institute for Development Studies (PIDS), 1997)
The growth of the Philippine economy has been erratic since 1980's. It is only until recently that it shows signs of catching up with the progress of its fellow Asian countries. Whether its recovery is sustainable at the aggregate level remains largely a question. Agriculture sector, however, is still bereft of such development exhibiting not only a fluctuating but also a relatively dismal performance. Comparison of Asian countries indicates that the Philippines have the most severe and most prolonged decline in the gross value added in agricultural exports. This is suspected to be due to the differences in the policy and institutional structures governing the sector. This paper analyzes the changing nature of price intervention and public expenditure policies affecting agriculture, the implications of WTO agricultural agreement on these policies and the factors in the political economy that help shape the nature of agricultural policies. Analysis shows price distortion and protection result to economy-wide inefficiencies through high consumer prices. The non-discriminating choice of policy instruments translates to inefficiency as well.
Keywords: 330; World Trade Organization; price intervention